Science and Governance of Ecosystems and Parks: the Everglades (USA) case study. - Mitchell, Carol L. (2019)
Science is key to solving the challenge of managing ecosystems for sustainable development. How do we achieve the benefits that result from the transformation and exploitation of ecosystems, and at the same time preserve ecosystem services and protected areas? In the ecosystem of the Everglades, a subtropical wetland located in South Florida (United States), an economic and environmental transformation occurred in the middle of the 20th century. Today, the Everglades Restoration Program is addressing the challenge of maintaining the benefits of the transformed ecosystem while at the same time protecting and restoring Everglades National Park. An analysis of the governance of this program highlights three important aspects of the system with respect to science. First, the primary decision-making body is the South Florida Ecosystem Restoration Task Force, a diverse group of 14 agency leads at the highest level of national, tribal, state and local government. Second, the role of science in the restoration program is written into the federal laws and regulations governing the program. Finally, all the member agencies of the Task Force employ qualified technicians and scientists whose work is to conduct, collect and synthesize scientific research. This system reduces the distance between scientists and decision makers. At the same time, the program’s governance system allows actors with less financial or political power to exercise power through their scientific results, thus achieving a balance between the economic benefits and environmental benefits of the program.